2021
DOI: 10.47895/amp.v55i2.2755
|View full text |Cite
|
Sign up to set email alerts
|

Patient Flow, Health Delivery Processes, and Areas for Improvement in the UP Health Service (UPHS) during May to June 2020 of the COVID-19 Pandemic

Abstract: Background. Workplace or employees’ clinics play a vital role in disease outbreaks as there could be an influx of sick personnel. Processes and patient flows during pandemics should be documented to identify good practices and sources of operational inefficiencies. Objective. To describe the patient flow, health delivery processes, and areas for improvement at the UPHS during the early phase of the COVID-19 pandemic from May to June 2020. Methods. This was a cross-sectional study involving patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Staff: maintaining mental health of employees (53), reducing burnout (53), training of employees (30,36), training of skilled workers (36, 54) and exible (55,56), giving incentives to effective employees (53), timely monitoring of performance (15), training other categories (36), employing retired forces (15,36).…”
Section: Optimal Management Of Capacities and Resourcesmentioning
confidence: 99%
“…Staff: maintaining mental health of employees (53), reducing burnout (53), training of employees (30,36), training of skilled workers (36, 54) and exible (55,56), giving incentives to effective employees (53), timely monitoring of performance (15), training other categories (36), employing retired forces (15,36).…”
Section: Optimal Management Of Capacities and Resourcesmentioning
confidence: 99%
“…17 Another study by Laviña et al during the pandemic in 2021 showed a mean turnaround time of 109 minutes with a standard deviation of 39.2 minutes. 18 Using the difference between mean turnaround time in the two studies of 8 minutes, the computed sample size for this study is 342 participants divided equally into the prepandemic and pandemic period (171 participants each).…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…A study by Cenizal et al in 2020 set in the pre-pandemic time showed mean turnaround time of 117 minutes while another study done during the pandemic by Laviña et al in 2019 showed a mean turnaround time of 109 minutes. 17,18 This may be attributed to differences in setup, system processes, and variances among physicians and patients. In our study, maintenance medication refills, requests for medical certification, and interpretation of laboratories were the usual reasons for consults with shorter turnaround times.…”
Section: Turnaround Time In the Primary Care Systemmentioning
confidence: 99%
See 2 more Smart Citations